Long-chain PtCu nano-bead material and application thereof
A one-step hydrothermal method synthesizes long-chain PtCu nanobeads with ultrafine nanoparticles, addressing the limitations of platinum-based catalysts by enhancing catalytic performance and stability for formic acid oxidation and hydrogen evolution.
Patent Information
- Application Number
- CN202410752672.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-12
- Publication Date
- 2025-01-03
AI Technical Summary
The high cost and limited reserves of platinum-based catalysts hinder the large-scale commercial use of hydrogen production and formic acid oxidation, and existing PtCu alloy catalysts face challenges in achieving high performance and stability for these reactions.
A long-chain PtCu nanobead material is synthesized via a one-step hydrothermal method using hexadecyltrimethylammonium chloride as a surfactant, 1-naphthylacetamide as a morphology directing agent, and formaldehyde as a reducing agent, resulting in ultrafine nanoparticles connected in a linear structure, enhancing catalytic activity and stability.
The method produces a catalyst with uniform morphology, large specific surface area, and abundant active sites, demonstrating excellent electrocatalytic activity and stability for formic acid oxidation and hydrogen evolution reactions, suitable for large-scale production.
Smart Images

Figure CN119237755A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of precious metal nanomaterials, and in particular relates to a long-chain PtCu nanobead material and application thereof. Background Art
[0002] The increasing depletion of traditional fossil fuels and serious environmental degradation have stimulated great research interest in developing sustainable and efficient energy conversion and storage technologies, such as regenerative fuel cells and hydrogen energy. At present, hydrogen production by water electrolysis is still highly dependent on Pt-based precious metal catalysts, but the high price and limited reserves of precious metals have seriously hindered large-scale commercial use. Therefore, the development of new catalysts that are cheaper and more efficient has become a hot topic.
[0003] One of the effective strategies to improve the efficiency of Pt catalysts is to combine Pt with other cheap metals to form a uniform alloy catalyst. PtCu alloy effectively improves the shortcomings of platinum such as easy poisoning, poor durability, and high cost, and effectively utilizes the synergistic effect and structural advantages of the alloy to enhance the activity and structural stability of the catalyst. However, it is still a great challenge to prepare high-performance and high-stability Pt-based nanobead catalysts and apply them to formic acid oxidation and hydrogen evolution reactions. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a long-chain PtCu nanobead material and its application. The long-chain PtCu nanobeads prepared by the method through a one-step hydrothermal method are specifically composed of ultrafine nanoparticles. The preparation method is not only simple and efficient, and the morphology is uniform, but also the catalyst has abundant active sites, and exhibits excellent electrocatalytic activity and stability for formic acid oxidation (FAOR) and hydrogen evolution reaction (HER), so as to meet the requirements of application and development in related fields.
[0005] In order to solve the problems of the prior art, the present invention adopts the following technical solutions: A long-chain PtCu nanobead material, hexadecyltrimethylammonium chloride as a surfactant and 1-naphthylacetamide as a morphology directing agent, after dissolution, Pt salt and Cu salt are added as metal precursors, and then a dispersant and a reducing agent are added, and a long-chain PtCu nanobead material is obtained through a one-step hydrothermal reaction; the long-chain PtCu nanobead material is composed of a plurality of round beads with a diameter of 20 nm connected in series into a line, wherein the round beads are assembled from a plurality of ultrafine nanoparticles with a diameter of 3 nm.
[0006] As an improvement, the solvent used for dissolution is water.
[0007] As an improvement, the reducing agent is formaldehyde solution; and the dispersing agent is polyvinyl pyrrolidone.
[0008] As an improvement, the molar ratio of the sum of the hexadecyltrimethylammonium chloride, 1-naphthylacetamide, the Pt salt precursor and the Cu salt precursor is 1-100:1-100:1.
[0009] As an improvement, the Pt salt is H2PtCl6, K2PtCl6 or K2PtCl4; the Cu salt is CuCl2 or Cu(NO3)2.
[0010] A further improvement is that the molar ratio of the Pt salt to the Cu salt is 0.01-100:1.
[0011] As an improvement, the hydrothermal reaction temperature is 100-200°C, and the reaction time is 3h-8h.
[0012] Application of any of the above long-chain PtCu nanobeads as catalysts for formic acid oxidation (FAOR) and hydrogen evolution reaction (HER).
[0013] The present invention forms a bimetallic alloy catalyst by introducing other metals Cu into Pt, and utilizes the synergistic effect between metals to adjust the electronic state of Pt, change the local coordination environment, and improve the catalytic activity. Specifically, the long-chain PtCu nanobeads prepared by the present invention have the structural unit of ultrafine nanoparticles, exposing more active sites. In addition to component regulation, morphology regulation is also an important factor affecting catalytic performance, accelerating the transmission and diffusion of substances and improving reaction kinetics. Beneficial Effects
[0014] Compared with the prior art, the long-chain PtCu nanobead material and its application in the present invention have the following advantages: 1) Compared with the traditional preparation method, the present invention synthesizes a long-chain PtCu nanobead catalyst composed of ultrafine nanoparticles by a simple one-step hydrothermal method, which has uniform morphology, simple process and is conducive to large-scale production.
[0015] 2) The single particle size of the long-chain PtCu nanobeads prepared by the present invention is 20 nm, and the single particle in the nanobeads is 3 nm, with a large specific surface area and certain pores.
[0016] 3) The long-chain PtCu nanobeads prepared by the present invention exhibit excellent catalytic activity and stability for formic acid oxidation and acidic hydrogen evolution reaction, and have great application potential in actual fuel cell devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is the TEM spectrum of the long-chain PtCu nanobeads prepared in Example 1 of the present invention; Figure 2This is the SEM spectrum of the long-chain PtCu nanobeads prepared in Example 1 of the present invention; Figure 3 This is the HRTEM spectrum of the long-chain PtCu nanobeads prepared in Example 1 of the present invention; Figure 4 is the XRD pattern of the long-chain PtCu nanobeads prepared in Example 1 of the present invention; Figure 5 This is the EDS spectrum of the long-chain PtCu nanobeads prepared in Example 1 of the present invention; Figure 6 It is a test spectrum of formic acid oxidation performance of the long-chain PtCu nanobeads prepared by the present invention and a comparative sample; Figure 7 It is a test spectrum of the acidic hydrogen evolution performance of the long-chain PtCu nanobeads prepared by the present invention and the comparative sample; Figure 8 It is a test spectrum of the acidic hydrogen evolution stability of the long-chain PtCu nanobeads prepared by the present invention. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further described in detail below through specific embodiments. Example 1
[0019] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead catalyst material.
[0020] TEM, HRTEM, SEM and XRD techniques were used to physically characterize the long-chain PtCu nanobead materials.
[0021] From TEM ( Figure 1 ) and SEM ( Figure 2 ) spectrum, it can be seen that the long-chain PtCu nanobead material can provide a larger specific surface area and more active sites. From the further magnified HRTEM ( Figure 3 ) spectrum, it can be seen that the long-chain PtCu nanobead material is composed of ultrafine nanoparticles. Figure 4 Figure 3 is the XRD pattern of long-chain PtCu nanobead material. The positions of all diffraction peaks are between the standard peaks of pure Pt (JCPDS: 04-0802) and pure Cu (JCPDS: 04-0836), proving the successful formation of PtCu alloy. Figure 5 It is the EDS spectrum of the long-chain PtCu nanobead material, showing the percentage of Pt and Cu in the PtCu nanobowl. Example 2
[0022] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 3
[0023] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 4
[0024] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 5
[0025] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 6
[0026] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 7
[0027] A method for preparing long-chain PtCu nanobeads comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 8
[0028] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 9
[0029] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material. Example 10
[0030] A long-chain PtCu nanobead material comprises the following steps: 1) Preparation of reaction solution: 180 mg CTAC was dissolved in 9 mL water. After it was completely dissolved, 91.11 mg 1-naphthylacetamide was added. After it was completely dissolved, 0.5 mL 0.05 M H2PtCl6 solution and 0.5 mL 0.05 M CuCl2 solution were added. After stirring and mixing, 400 mg polyvinyl pyrrolidone with a molecular weight of 30,000 and 1.5 mL formaldehyde solution were added. 2) Preparation of long-chain PtCu nanobeads: The solution prepared in step 1 was placed in an oven at 120 °C for 5 h, cooled to room temperature, centrifuged at 15,000 rpm for 15 min, and ultrasonically washed the precipitate three times with an ethanol-water solution with a volume ratio of 1:1, and freeze-dried to obtain the long-chain PtCu nanobead material.
[0031] The formic acid oxidation performance of the catalyst was tested. The specific steps are as follows: 2 mg of the catalyst was weighed and dispersed in 1 mL of an ethanol-water mixed solution (the volume ratio of water to alcohol was 3:1) by ultrasonic dispersion to prepare a catalyst solution. Subsequently, 8 μL of the catalyst solution was dropped on the surface of the glassy carbon electrode and placed in an oven at 40 °C to dry. After completion, 3 μL of the Nafion solution was dropped on the glassy carbon electrode loaded with the catalyst. Before the FAOR test, N2 was passed into the 0.5 M H2SO4 electrolyte for at least 20 min until it was saturated, and a cyclic voltammetry (CV) curve test was performed with a scan rate of 50 mV s -1 Then, the samples were tested in a N2-saturated 1.0 M HClO4 + 1.0 MHCOOH solution at a scan rate of 50 mV s -1 .
[0032] Based on the preparation process of Example 1, the composition ratio of the precursor was adjusted to prepare a comparative sample, and then the performance test was performed. The results are as follows: Figure 6-8 As shown, the comparative sample Pt3Cu is prepared by adding 0.75 mL 0.05 M H2PtCl6 solution and 0.25 mL 0.05 M CuCl2 solution, and the comparative sample PtCu3 is prepared by adding 0.25 mL 0.05 M H2PtCl6 solution and 0.75 mL 0.05M CuCl2 solution.
[0033] Figure 6 This is a test graph of formic acid oxidation performance of the long-chain PtCu nanobead catalyst and other comparison samples in 1.0 M HClO4 + 1.0 M HCOOH solution. It can be seen from the figure that the highest mass peak current of the long-chain PtCu nanobead material of the present invention reaches 3047 mA mg Pt -1 , better than commercial Pt black. The hydrogen evolution performance of the catalyst was tested, and the specific steps are as follows: 2 mg of the catalyst was weighed and dispersed in 1 mL of an ethanol-water mixed solution (the volume ratio of water to alcohol was 3:1) by ultrasonication to prepare a catalyst solution. Subsequently, 8 μL of the catalyst solution was dropped on the surface of the glassy carbon electrode and placed in an oven at 40 °C to dry. After completion, 3 μL of the Nafion solution was dropped on the glassy carbon electrode carrying the catalyst. Before the HER test, N2 was passed into the 0.5 M H2SO4 electrolyte for at least 20 min until it was saturated. Subsequently, the linear sweep voltammetry (LSV) test used in the HER test was carried out in this electrolyte, and the scan rate was 5 mV s -1 .
[0034] Figure 7 The long-chain PtCu nanobead catalyst and other comparison samples are shown in the hydrogen evolution performance test spectrum in 0.5 M H2SO4 solution. The long-chain PtCu nanobead material of the present invention has a hydrogen evolution performance of 10 mA∙cm -2 Only 14 mV overpotential is required, which is better than commercial Pt black.
[0035] Figure 8 The stability test of long-chain PtCu nanobeads in hydrogen evolution in 0.5 M H2SO4 solution shows that after 100,000 seconds of chronoamperometric test, the material performance of the long-chain PtCu nanobeads of the present invention is basically not attenuated, which is mainly attributed to the stable structure and composition of the long-chain PtCu nanobeads, which are suitable as hydrogen evolution catalysts and have broad application prospects.
[0036] The method is simple to operate, has mild conditions, and has a high yield, and can achieve large-scale production. The long-chain PtCu nanobeads prepared by the method of the present invention have the advantages of large specific surface area, rich active sites, etc., and have excellent electrocatalytic activity and stability for formic acid oxidation and acidic hydrogen evolution reaction.
Claims
1. A long-chain PtCu nanobead material, characterized in that: Hexadecyltrimethylammonium chloride is used as a surfactant and 1-naphthylacetamide is used as a morphology directing agent. After dissolution, Pt salt and Cu salt are added as metal precursors, and then a dispersant and a reducing agent are added. A long-chain PtCu nanobead material is obtained through a one-step hydrothermal reaction; the long-chain PtCu nanobead material is composed of a plurality of round beads with a diameter of 20 nm connected in series, wherein the round beads are assembled from a plurality of ultrafine nanoparticles with a diameter of 3 nm.
2. The long-chain PtCu nanobead according to claim 1, characterized in that: The solvent used for dissolving is water.
3. The long-chain PtCu nanobeads according to claim 1, characterized in that The reducing agent is formaldehyde solution, and the dispersing agent is polyvinyl pyrrolidone.
4. The long-chain PtCu nanobeads according to claim 1, characterized in that The molar ratio of the sum of the hexadecyltrimethylammonium chloride, 1-naphthylacetamide, the Pt salt precursor and the Cu salt precursor is 1-100:1-100:
1.
5. The long-chain PtCu nanobeads according to claim 1, characterized in that The Pt salt is H2PtCl6, K2PtCl6 or K2PtCl4; the Cu salt is CuCl2 or Cu(NO3)2.
6. The long-chain PtCu nanobeads according to claim 5, characterized in that The molar ratio of the Pt salt to the Cu salt is 0.01-100:
1.
7. The long-chain PtCu nanobeads according to claim 1, characterized in that The hydrothermal reaction temperature is 100° C. to 200° C., and the reaction time is 3 h to 8 h.
8. Use of the long-chain PtCu nanobead material according to any one of claims 1 to 7 as a catalyst in formic acid oxidation or acidic hydrogen evolution reaction.
